NSIC Rc298 The first released variety for irrigated lowland direct wet-seeded rice system (The Philippine Journal of Crop Science, 2014)
Seedling vigor, anaerobic germination, lodging resistance, resistance to major pests and diseases, and yield are the major traits that are considered in the development of new cultivars for direct wet-seeded rice system. Several genetic donors and breeding populations have been tested for these traits under field and laboratory conditions. NSIC Rc298 was derived from a cross between PR29253-96-1 and AR32-4-5-2 in 2002DS designated as PR34159. It was selected and advanced for several years until nomination to the National Cooperative Test in 2008. The breeding line, PR34159-13-1, passed the Multi-location Adaptation Trial in 2011 and recommended for release in 2012. NSIC Rc298 had a 5.6% yield advantage over PSB Rc82, a popular high-yielding variety in irrigated lowland. It has anaerobic germination tolerance which is a desirable trait for direct wet-seeding and with wide spectrum resistance to major insect pests and diseases. The grain quality is comparable to both PSB Rc82 and IR64. This is the first rice variety recommended for direct wet-seeding cultivation.